Medical assistance as a process. Application of a systemic approach to the study of the medical assistance. - Luis Alberto Corona Martínez (Medisur)
This article presents the concepts that give theoretical support to the character of the medical assistance as a process. From this point of view the analysis of the process is carried out following a systemic approach, allowing the identification of the components of the process: object- subject- objective-problem- method- content- material aids teaching form and result s, all of which form the eternal structure of the process. Teaching, investigative and assistencial implications of this process are present as well as its contribution for the medical practice of the new doctors.